Acquisitions and the Accelerated Shift to Digital in Academic Libraries in the UK: Reflecting on the Covid Experience at De Montfort University and Imperial College London. Issue 3 (3rd July 2021) - Brine, Alan; Knight, Andrew
Abstract: Summer 2020 witnessed a large-scale temporary release of content from the publishing community to support UK universities as they moved to online-only delivery, followed by a scramble by those institutions to maintain access to resources. This paper reflects on the experiences of De Montfort University and Imperial College libraries during this period as they supported the move to remote teaching. It focuses on the complexities experienced during this transitional period, and considers how the speed of these changes increased staff workloads, stretched budgets, and compelled acquisitions teams to act without always fully gathering evidence or strategically planning how new practices might work in the longer term. The authors, who sit on various national contract management and acquisitions strategy groups, examine the repercussions of navigating from an unplanned, accelerated digital shift to a more managed, sustainable paradigm, and contemplate how the advent of multimode teaching may impact on the way libraries are resourced.